2007
DOI: 10.1007/s10735-007-9113-6
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin 6C expression in innervated and denervated skeletal muscle

Abstract: Semaphorins are secreted or transmembrane proteins important for axonal guidance and for the structuring of neuronal systems. Semaphorin 6C, a transmembrane Semaphorin, has growth cone collapsing activity and is expressed in adult skeletal muscle. In the present study the expression of Semaphorin 6C mRNA and immunoreactivity has been compared in innervated and denervated mouse hind-limb and hemidiaphragm muscles. Microscopic localization of immunoreactivity was studied in innervated and denervated rat skeletal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…To eliminate the possibility that the Sfrp1-like immunoreactivity was unspecific, sections were first incubated with normal control goat IgG together with normal control rabbit IgG. Normal control IgGs from both species stained muscle endplates in a similar manner and the staining obtained was clearly co-localized and overlapping (results not shown, see Svensson et al 2008). Next, sections were incubated with the anti-Sfrp1 antibody together with normal goat IgG and the stainings observed, contrary to the case for the two Fig.…”
Section: Sfrp1 Immunoreactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…To eliminate the possibility that the Sfrp1-like immunoreactivity was unspecific, sections were first incubated with normal control goat IgG together with normal control rabbit IgG. Normal control IgGs from both species stained muscle endplates in a similar manner and the staining obtained was clearly co-localized and overlapping (results not shown, see Svensson et al 2008). Next, sections were incubated with the anti-Sfrp1 antibody together with normal goat IgG and the stainings observed, contrary to the case for the two Fig.…”
Section: Sfrp1 Immunoreactivitymentioning
confidence: 99%
“…Normal rabbit and goat IgGs (from non-immunized animals) can give a considerable staining of the endplate region of muscle fibers (Svensson et al 2008). The specificity of the staining observed with the Sfrp1 antibody was inferred by comparing the staining obtained with the Sfrp1 antibody and that observed with control IgGs (normal IgGs) from two different species (rabbit and goat).…”
Section: Specificity Of Sfrp1-like Immunoreactivitymentioning
confidence: 99%
“…In a recent work by Tatsumi et al (59), it was speculated that the increased expression of Sema3A observed in satellite cells in response to injury-induced muscle regeneration could serve a paracrine function regulating muscle innervation. Moreover, Sema6C was found to localize primarily at neuromuscular junctions in vivo, and the expression of Sema6C was reduced in response to denervation of skeletal muscle, indicating that other classes of semaphorins could be involved in neurogenesis of skeletal muscle (63).…”
Section: Dynamic Secretion Profile Of Tgf-␤1 -␤2 -␤3 and Associatementioning
confidence: 99%
“…on the other hand, it has been shown that both human Sema6c and Sema6d are expressed in the skeletal muscle, and that the expression of both semaphorin genes is downregulated following denervation (40). Furthermore, it was found that hSema6c is expressed in extrasynaptic as well as in perisynaptic regions of muscles, and that the protein is concentrated at neuromuscular junctions, suggesting a role of hSema6c in neuromuscular communication (41).…”
Section: Discussionmentioning
confidence: 99%